Reducing Disease Activity of Inflammatory Bowel Disease by Consumption of Plant-Based Foods and Nutrients - Antoniussen, Christian S.; Rasmussen, Henrik H.; Holst, Mette; Lauridsen, Charlotte (Frontiers in Nutrition, 2021)
Inflammatory bowel disease is a chronic and recurring inflammatory condition of the gastrointestinal tract encompassing ulcerative colitis and Crohn’s disease. Although the pathogenesis of inflammatory bowel disease remains to be fully elucidated, environmental factors such as diet are believed to play a pivotal role in the onset and management of inflammatory bowel disease. Diet is thought to play an essential role in intestinal inflammation due to its regulatory effects on the microbiota, gut immune system, and epithelial barrier function. Although the evidence remains insufficient to draw firm conclusions on the role of specific dietary components and these gastrointestinal diseases, studies have suggested that a Western diet with high intakes of total fats, omega-6 fatty acids, and meat have been associated with intestinal inflammation and relapse of inflammatory bowel disease. In contrast to a Western diet, plant-based diets often result in a reduced intake of total fats and meats and an increased intake of plant fibers which may contribute to reduced intestinal inflammation. This review critically examines the influence of plant-based dietary components on the clinical disease course of inflammatory bowel disease. Furthermore, this review discusses the benefits and possible limitations of plant-derived dietary components in the treatment of inflammatory bowel disease while addressing the principal type of disease and the anatomic enteric site of inflammation. Finally, this review points out important directions for future research on the role of diet in inflammatory bowel disease. A better understanding of the role of diet and intestinal inflammation may pave the way for novel dietary interventions and specific foods- or food supplements, which can support the treatment of inflammatory bowel disease.